Visionary Kyai Leadership: An Integrative Solution for Islamic Tradition and Modernity - Arifin, Misbahul; Jazilurrahman, Jazilurrahman; Nordin, Norazah; Rahman, Ikhwan (INJIES: Journal of Islamic Education Studies, 2025)
This research explores the role of visionary kyai leadership in integrating Islamic traditions with modernity at Pondok Pesantren Nurul Jadid, Probolinggo, East Java. This tension often creates a dichotomy: on one side, pesantren that exclusively preserve traditions with little adaptation, and on the other side, pesantren that become overly modernized to the extent of diluting their traditional identity. The study aims to analyze how visionary leadership preserves Islamic traditions while simultaneously adopting innovations to strengthen the quality and competitiveness of Islamic education. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and documentation, then analyzed with Miles and Huberman’s interactive model. The findings reveal that Islamic traditions such as the study of classical texts, religious rituals, and moral values remain the pesantren’s foundation, while modern practices like curriculum reform, digitalization, and management innovation are selectively adopted under visionary leadership. The integration of tradition and modernity emerges not as a contradiction but as a synergy, creating an educational model that is both authentic and adaptive. The implications suggest that visionary kyai leadership provides a strategic framework for other Islamic educational institutions to maintain cultural authenticity while effectively addressing contemporary challenges.